Vitex agnus-castus: Botanical features and area, chemical composition of fruit, pharmacological properties, and medicinal uses - Grigory Vasilievich Adamov, Tamara Danilovna Rendyuk, Olga Leonidovna Saybel, Tamara Darizhapovna Dargaeva, Andrey Nikolaevich Tsitsilin, Dmitry Olegovich Bokov (Journal of Applied Pharmaceutical Science, 2022)
This review is based on published data on the fruits of the chaste tree (Vitex agnus-castus L.), a traditional medicinal plant used to treat premenstrual syndrome (PMS). The review summarizes and analyzes the existing literature on the chemical composition and pharmacological properties of the fruit extract and its individual chemical compounds. According to the current data, the presence of 20 flavonoids, 10 iridoids, 11 phenolic acids, three diterpene alkaloids, and 12 terpenes was confirmed in the extract of Vitex fruits. Many of these compounds exhibit pharmacological activity according to the results of preclinical studies. Thus, various authors have confirmed the presence of dopaminergic, opioid, estrogenic, immunomodulatory, antineoplastic, and antioxidant activity. It is assumed that the cumulative effect of several chemical compounds also has beneficial effects on the complex regulation of the female reproductive system. In this review, special attention is paid to data obtained from clinical trials because they are the most important and reliable studies of drug efficacy and safety. Nine clinical studies that examined the effect of preparations based on chaste tree fruit extract on the female reproductive system are reviewed. Studies have shown that the fruits of the chaste tree significantly reduce the symptoms of PMS, normalize the menstrual cycle, and lower prolactin levels. The use of Vitex is often preferable due to its high efficacy, long-term and short-term tolerance, and positive effect on the female reproductive system, including fertility.
Keywords: Vitex agnus-castus L., biologically active substances, fruits, premenstrual syndrome, pharmacologic properties